2017
DOI: 10.1088/1361-648x/aa9c12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for confinement induced phase separation in ethanol–water mixture: a positron annihilation study

Abstract: We report an experimental evidence for the phase separation of ethanol-water mixture confined in mesoporous silica with different pore size using positron annihilation lifetime spectroscopy (PALS). A bulk-like liquid in the core of the pore and a distinct interfacial region near the pore surface have been identified based on ortho-positronium lifetime components. The lifetime corresponding to the core liquid shows similar behavior to the bulk liquid mixture while the interfacial lifetime shows an abrupt rise w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…They showed that a small fraction of the ethanol molecules seemed to be anchored at the silica surface. 34 A similar result was also established by Guo et al 14 who have studied confinement of the ethanol-water mixture between two planar silica walls. A partial and local separation between water and ethanol close to the silica surface was thus evidenced.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…They showed that a small fraction of the ethanol molecules seemed to be anchored at the silica surface. 34 A similar result was also established by Guo et al 14 who have studied confinement of the ethanol-water mixture between two planar silica walls. A partial and local separation between water and ethanol close to the silica surface was thus evidenced.…”
Section: Introductionsupporting
confidence: 74%
“…Whereas these effects have been largely investigated in the case of confined single components [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and immiscible binary mixtures, [28][29][30] less works have been devoted to the confinement of miscible liquid mixtures. 15,[31][32][33] Recently, Muthulakshmi et al 34 reported an experimental evidence of a partial phase separation of an ethanol-water mixture confined in mesoporous silica using positron annihilation lifetime spectroscopy. They showed that a small fraction of the ethanol molecules seemed to be anchored at the silica surface.…”
Section: Introductionmentioning
confidence: 99%
“…universally, both for alcohol-water mixtures [7][8][9][10][11] and macromolecules [4,5] To achieve these aims, the stability theory is indispensable, because the study of preferential adsorption on its own cannot give a complete insight into phase separation for the following reasons. Here, adsorption refers to 〈𝑁 𝑚 𝑁 1 〉 and 〈𝑁 𝑚 𝑁 2 〉, whereas, from Eq.…”
Section: Phase Separation Via Preferential Adsorption and Depletion Interactionmentioning
confidence: 99%
“…Aqueous biomolecular solutions stable in macroscopic bulk, such as the ones containing DNA, PEG and NaCl [4] or DNA and alginate [5], undergo phase transition when confined in a droplet, and increasingly so as the droplet size decreases [4,5]. Simple solution mixtures [6], even ethanol-water [7][8][9][10][11] mixtures, go through phase separation under confinement. Thus, confinement may affect phase stability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the phase behavior can be affected by such multitude of interactions [ 41 ]. In particular, several studies found an increased tendency for microphase separation of confined binary mixtures as a consequence of preferential interactions with the pore walls [ 42 , 43 , 44 , 45 ]. Furthermore, it was reported that the dependence of the glass transition temperature on the composition differs for confined and bulk hydrogen-bonded mixtures [ 38 ].…”
Section: Introductionmentioning
confidence: 99%